1996
DOI: 10.1002/1529-0131(199604)9:2<126::aid-anr1790090209>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of dexamethasone iontophoresis for the treatment of rheumatoid arthritic knees: A pilot study

Abstract: Objective. To examine the efficacy of dexamethasone sodium phosphate (DEX) iontophoresis for the treatment of rheumatoid arthritis (RA) of the knee, and to obtain statistical information for a future randomized controlled trial (RCT). Methods. Ten subjects with RA, ranging in age from 34–75, were randomly assigned to either the experimental or placebo group. Iontophoresis treatments were given to both groups on days 1, 3, and 5. Five subjects in the experimental group received a mixture of 1 ml of DEX (4 mg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 17 publications
(8 reference statements)
1
19
0
Order By: Relevance
“…Treatment modalities of RA include analgesic drugs, non-steroidal anti-inflammatory drugs, physical therapy, electrotherapy, steroid injections, ultrasound, iontophoresis, and low intensity laser therapy [13][14][15] . Low intensity laser therapy has many benefits, such as microcirculation enhancement, vasodilatation, tissue metabolism improvement, activation of angiogenesis, nerve regeneration, and analgesic effects at the tissue level [16][17][18] .…”
Section: Introductionsupporting
confidence: 71%
“…Treatment modalities of RA include analgesic drugs, non-steroidal anti-inflammatory drugs, physical therapy, electrotherapy, steroid injections, ultrasound, iontophoresis, and low intensity laser therapy [13][14][15] . Low intensity laser therapy has many benefits, such as microcirculation enhancement, vasodilatation, tissue metabolism improvement, activation of angiogenesis, nerve regeneration, and analgesic effects at the tissue level [16][17][18] .…”
Section: Introductionsupporting
confidence: 71%
“…[12] Phonophoresis (PH) is a technique that employs the use of ultrasound waves to enhance percutaneous absorption of drug delivery similar to iontophoresis. [11,13] Phonophoresis was first used to treat polyarthritis of the hand by delivery of hydrocortisone ointment into inflamed areas in 1954. [14] Since then it has been reported to be used in the treatment of various dermatological and musculoskeletal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Since then it has been reported to be used in the treatment of various dermatological and musculoskeletal disorders. [13][14][15][16] Previous studies have established the therapeutic effectiveness of various types of NSAIDs gel PH on both acute and chronic musculoskeletal pain and disorders. [17][18][19][20] Because of the established efficacy of this modality, there are several ongoing studies with some controversies from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of its use for JIA‐associated TMJ involvement, DIP has been employed for the treatment of arthritis in the past. In an earlier pilot study, adult patients with rheumatoid arthritis experienced a reduction in knee pain with DIP to the knee joints (16). Likewise, Ozgocmen et al showed that triamcinolone iontophoresis resulted in a reduction in synovial tissue vascularity on power Doppler sonography, a surrogate for reduced inflammation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Low‐grade electric currents lead to the dissociation of hydrophilic medications into ions that move to penetrate deeper anatomic structures (15). DIP therapy has been utilized for more than 30 years to treat various musculoskeletal conditions, including tendinitis, epicondylitis, enthesitis, and inflammatory peripheral arthritis (16–19). Given the relatively superficial position of the TMJ, we hypothesized that DIP is beneficial for the treatment of the TMJ of children with JIA.…”
Section: Introductionmentioning
confidence: 99%